The Effect of Credit Distribution and an Educated Workforce on Economic Growth in Indonesia - M. Rizky Mahaputra; M. Ridho Mahaputra (Greenation International Journal of Economics and Accounting, 2023)
The purpose of this research is to analyze the effect of lending and an educated workforce on economic growth in Indonesia. This study uses secondary data, namely Credit Distribution and Educated Labor Against Economic Growth in Indonesia in 1982-2012 from the Indonesian Central Bureau of Statistics and Bank Indonesia. This study uses a multiple linear regression model. The results of the study show that (1) Credit Distribution has a significant effect on Economic Growth in Indonesia with a probability value of 0.0000 <?=0.05 (2) Educated Workforce has a significant effect on Economic Growth in Indonesia where the probability value is 0.0000> ?=0.05 Credit Distribution and Labor Educated work has a joint effect on economic growth in Indonesia by 99 percent.